2014
DOI: 10.4049/jimmunol.1300891
|View full text |Cite
|
Sign up to set email alerts
|

Immune Suppression via Glucocorticoid-Stimulated Monocytes: A Novel Mechanism To Cope with Inflammation

Abstract: Glucocorticoids (GCs) are used as first-line therapies for generalized suppression of inflammation (e.g., allergies or autoimmune diseases), but their long-term use is limited by severe side effects. Our previous work revealed that GCs induced a stable anti-inflammatory phenotype in monocytes, the GC-stimulated monocytes (GCsMs) that we exploited for targeted GC-mediated therapeutic effects. We demonstrate that GCsMs interact with T cells in suppressing proliferation, as well as cytokine release of CD8+ and, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
2
23
1
1
Order By: Relevance
“…The same study also showed that in the T cell transfer colitis model, CD4 + Foxp3 + Tregs accumulate locally in the colon after treatment with GCsMs and that repetitive stimulation of naive splenic T cells with GCsMs induces Tregs in vitro. However, Tregs also did not expand in draining MLNs and LPMCs of animals treated with GCsMs during T cell transfer colitis (68). Collectively, GMaMs induce the differentiation of CD4 + Foxp3 + Tregs in vitro, but we found no evidence that the GMaM-mediated protection from colitis is facilitated via expansion of mucosal Tregs in vivo.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The same study also showed that in the T cell transfer colitis model, CD4 + Foxp3 + Tregs accumulate locally in the colon after treatment with GCsMs and that repetitive stimulation of naive splenic T cells with GCsMs induces Tregs in vitro. However, Tregs also did not expand in draining MLNs and LPMCs of animals treated with GCsMs during T cell transfer colitis (68). Collectively, GMaMs induce the differentiation of CD4 + Foxp3 + Tregs in vitro, but we found no evidence that the GMaM-mediated protection from colitis is facilitated via expansion of mucosal Tregs in vivo.…”
Section: Discussioncontrasting
confidence: 66%
“…Interestingly, it has recently been shown that the therapeutic transfer of glucocorticoid-stimulated monocytes (GCsMs) in the T cell transfer colitis model also resulted in a strongly downregulated release of IFN-g by T cells from LPMCs and MLNs. The production of IL-4 and IL-13 was not influenced in single-cell suspensions from LPMCs and MLNs after treatment of mice with injection of GCsMs, which is also in contrast with the in vitro system, where cytokine production of IFN-g, IL-4, and IL-13 by T cells was significantly regulated in cocultures with GCsMs (68). The same study also showed that in the T cell transfer colitis model, CD4 + Foxp3 + Tregs accumulate locally in the colon after treatment with GCsMs and that repetitive stimulation of naive splenic T cells with GCsMs induces Tregs in vitro.…”
Section: Discussionmentioning
confidence: 56%
“…Most features of the stroke-induced immunodepression may favor tolerogenic immune responses. Thus, catecholamines can inhibit the antigen-presenting capability via β2-adrenoceptors [135][136][137], corticosteroids inhibit the production of inflammatory cytokines in APCs and induce the development of tolerogenic APCs [138,139], and glucocorticoid-stimulated monocytes reduce the release of interferon-γ and IL-17 in lymphocytes, favoring the generation of Tregs [140]. IL-10 also inhibits autoimmune reactions acting on several immune cells, including APCs inducing anergic T cells that are able to suppress activation, and function of T cells in an antigen-specific manner [141].…”
Section: Sai and Brain Damagementioning
confidence: 99%
“…Взаимодей-ствуя с β2-адренорецепторами, катехоламины подавляют антигенпрезентирующую функцию дендритных клеток и моноцитов; индуцируют толерогенные дендритные клетки, способные вызывать анергию Т-лимфоцитов и генерацию Тreg [44]. Активированные глюкокортикоидами моноциты подавляют в Т-клетках продукцию IFNγ и IL-17 и также индуцируют генерацию Тreg [126]. Возрастание уровня указанных медиаторов вызывает апоптоз лимфоцитов и Th1/Th2-пере-ключение, атрофию первичных и вторичных лимфоидных органов, индукцию регуляторных Т-клеток [87,88,94].…”
Section: системные проявления иммунного ответа на острую ишемиюunclassified